1987
DOI: 10.1111/j.1445-2197.1987.tb01281.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of an Iodophor‐impregnated Plastic Incise Drape in Abdominal Surgery—a Controlled Clinical Trial

Abstract: A prospective randomized clinical trial comparing the use of a new iodophor‐impregnated incise drape with a standard skin preparation technique in 1102 patients undergoing abdominal surgical procedures is reported. The effect of the incise drape on wound bacterial contamination and subsequent wound infections is compared. The iodophor‐impregnated plastic incise drape reduced the contamination of the wound. In particular, isolates of normal skin organisms were less frequent when the drape was used in clean and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Another study reported no difference in postoperative wound infection rates when comparing randomized cohorts of drape and no-drape groups in 120 patients with acute hip fractures [2]. Finally, a third study also revealed that there is no difference in actual wound infection between iodophor-impregnated drape and in wounds in which drapes were not used [3]. This suggests that, even though basic science studies reveal decreased contamination when assessing colony counts, this may not translate into actual infection.…”
Section: Discussionmentioning
confidence: 71%
“…Another study reported no difference in postoperative wound infection rates when comparing randomized cohorts of drape and no-drape groups in 120 patients with acute hip fractures [2]. Finally, a third study also revealed that there is no difference in actual wound infection between iodophor-impregnated drape and in wounds in which drapes were not used [3]. This suggests that, even though basic science studies reveal decreased contamination when assessing colony counts, this may not translate into actual infection.…”
Section: Discussionmentioning
confidence: 71%
“…Dewan et al found no difference between the SSI rates for the patients on whom the iodophor drape was used and those patients on whom the drape was not used. However, they found that isolates of normal skin organisms were less frequent when the drape was used in clean and cleancontaminated procedures [6]. In the guideline for prevention of SSI published by the Hospital Infection Control Practices Advisory Committee, there was no evidence that specific reductions in microbial counts on the skin (obtained with use of common preoperative skin-preparation products) lowered the incidence of SSI [7].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the iodine-impregnated drape reduced wound contamination [15]. Analogous results were shown by the comparison between preoperative antiseptics with PVP iodine/alcohol (betadine), identical antiseptics with subsequent use of the antiseptic incision drape and use of the drape alone [16].…”
Section: Effects On the Skin Flora And Wound Contaminationmentioning
confidence: 97%
“…The use of the antiseptic drape in comparison to standard skin antiseptics without using the drape (n=1,102) did reduce wound contamination in abdominal and cardiac surgery; however the SSI rate did not differ significantly [15]. …”
Section: Influence On the Ssi Ratementioning
confidence: 99%